Anterior Ischemic Optical Neuropathy in Children on Chronic Peritoneal Dialysis: Report of 7 Cases. Issue 2 (March 2015) - Di Zazzo, Giacomo; Guzzo, Isabella; De Galasso, Lara; Fortunato, Michele; Leozappa, Giovanna; Peruzzi, Licia; Vidal, Enrico; Corrado, Ciro; Verrina, Enrico; Picca, Stefano; Emma, Francesco
Background: Anterior ischemic optic neuropathy (AION) is characterized by infarction of the optic nerve head due to hypoperfusion of the posterior ciliary arteries and causes sudden blindness in adults on chronic dialysis, but has rarely been described in children. Unlike adults, children do not have comorbidities related to aging. Methods: We retrospectively analyzed data of 7 children on nocturnal continuous cycling peritoneal dialysis (CCPD) who developed AION identified within the Italian Registry of Pediatric Chronic Dialysis. We also summarized data from 10 cases reported in the literature. Results: Our 7 patients suffered from acute onset bilateral blindness. Their mean age was 3.2 years and chronic hypotension had been observed prior the AION in 3 of the 7 children. Low systolic blood pressure (SBP) was associated with higher risk of developing AION according to statistical analysis. None recovered completely. In total, 11 out of 16 experienced a partial recovery and no clear evidence emerged favoring specific treatments. Conclusions: Hypotensive children treated with CCPD are at increased risk of developing AION, which often results in irreversible blindness.